Intensive teaching of mathematics while sequestering teaching hours - Nurlybayev Аманжол; Bekzhigitova Гульназ (Рroblems of engineering and professional education, 2023)
The article is devoted to the case of further improvement of materials of school mathematics, including algebra textbook. It is supported by many data that the introduction of elements of combinatorics, balances and inequalities of n-numbers and arithmetic-geometric progression (AGP) into educational materials greatly contributes to the improvement of students’ mathematical readiness.